2016
DOI: 10.1007/s40615-016-0221-4
|View full text |Cite
|
Sign up to set email alerts
|

Jazzin’ Healthy: Interdisciplinary Health Outreach Events Focused on Disease Prevention and Health Promotion

Abstract: These interdisciplinary outreach events provided health information and access to care in a novel setting and led to a high rate of planned health behavior changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…It remains unclear then, if participants attended the events as a means to improve poor health, or if attendance was primarily among individuals that were already largely in good health, and were simply attending for personal entertainment. Similar to previous findings, attendees appear to be alreadyactive individuals, interested and motivated to improve health outcomes (22). It is possible that the large-scale, multi-activity iterations of the FHTC events were more appealing to alreadyhealthy, already-active individuals rather than serve to identify at-risk individuals.…”
Section: Lessons Learnedsupporting
confidence: 76%
See 2 more Smart Citations
“…It remains unclear then, if participants attended the events as a means to improve poor health, or if attendance was primarily among individuals that were already largely in good health, and were simply attending for personal entertainment. Similar to previous findings, attendees appear to be alreadyactive individuals, interested and motivated to improve health outcomes (22). It is possible that the large-scale, multi-activity iterations of the FHTC events were more appealing to alreadyhealthy, already-active individuals rather than serve to identify at-risk individuals.…”
Section: Lessons Learnedsupporting
confidence: 76%
“…Community-based health promotion events have shown that the use of health screening, counseling services, clinics, and health education are effective tools for promoting health behaviors and awareness (21)(22)(23). Recent studies have shown that health promotion events have been successful at increasing awareness of healthy lifestyle opportunities, identifying health risk factors, and assessing readiness to change (22,24). However, health behaviors and health risk factors may already be known to the public, due to long-term promotion by public health campaigns (22).…”
Section: The Potential Influence Of Sports Franchisesmentioning
confidence: 99%
See 1 more Smart Citation
“…From screenings for chronic conditions such as hypertension and diabetes to undiagnosed HIV infections and diabetic retinopathy, the accessibility of community-based pharmacists creates a natural touch point for health screenings for patients who would otherwise not present to a physician’s office. Our results also reveal that pharmacists are also providing screening services beyond the four walls of the pharmacy at after-school programs [ 30 ], college campuses [ 31 ], and health fairs [ 32 ]. As community pharmacy continues to expand services offered, preventive care appears to be an accessible way pharmacists can work to reduce health disparities in their communities.…”
Section: Discussionmentioning
confidence: 93%
“…The inclusion of disciplines beyond the health professional workforce to address community health education endeavours may provide new opportunities not realised previously. Isaacs et al (2017) created an interdisciplinary team partnership to deliver health education to primarily African American community members through a university concert series. The interdisciplinary team included members from the following disciplines: health information technology, medicine, nursing, nutrition, occupational therapy, optometry, pharmacy and public health.…”
Section: Introductionmentioning
confidence: 99%